2002
DOI: 10.1046/j.1365-2036.2002.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal markers in the assessment of activity in inflammatory bowel disease

Abstract: The fundamental pathological process behind ulcerative colitis and Crohn's disease is intestinal inflammation. As the precise cause of this is not yet completely understood, current treatment strategies are aimed at reducing or eliminating the inflammation. Endoscopic examination and histological analysis of biopsy specimens remain the `gold standard' methods for detecting and quantifying bowel inflammation; however, these techniques are costly, invasive, and repeated examinations are unpopular with patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 41 publications
0
67
0
5
Order By: Relevance
“…Moreover, the monomers S100A8 and S100A9 have been detected in urine and renal epithelial cells as well (8,9). In neutrophil cytoplasm it adds up to 60% of the cytosolic proteins (10). Calprotectin is an activator of the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the monomers S100A8 and S100A9 have been detected in urine and renal epithelial cells as well (8,9). In neutrophil cytoplasm it adds up to 60% of the cytosolic proteins (10). Calprotectin is an activator of the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is a measure of local inflammatory activity that seems to be unaffected by a variety of conditions that result in an elevation of systemic inflammation (13,18). Second, calprotectin shows an excellent stability at room temperature for up to as long as 1 week (10,19,20). The quantification is done using the inexpensive and easy ELISA technique.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Calprotectin has antimicrobial 8 -14 and antiproliferative 15 -17 properties and appears to play a regulatory role in the inflammatory process. 18 -20 Faecal calprotectin (f-Cp) concentrations are raised in patients with intestinal mucosal inflammation, 21 whereas levels in patients with IBS are similar to those in healthy individuals. 22 -24 F-Cp measurement, therefore, provides a non-invasive marker for distinguishing IBD from IBS, thereby reducing the number of unnecessary endoscopic and radiological investigations in patients presenting with chronic diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Blood and faecal markers could fulfil these criteria and may be a good diagnostic alternative. CRP, Tumour Necrosis Factor Alpha (TNFα) and microalbuminuria have been identified as useful markers of disease activity in human patients with IBD (Poullis et al, 2002;McCann et al, 2007). Nevertheless, McCann et al (2007) reported that there was no Correlation Between those parameters and clinical symptoms (CIBDAI) and his to pathological findings.…”
Section: Diagnosismentioning
confidence: 99%
“…The criteria have been developed for qualitative evaluation of endoscopic mucosal appearances Table 3 (Slovak et al, 2014). In addition, his to pathological analysis is another method for the diagnosis of IBD and objective criteria are established in dogs Table 4 (Poullis et al, 2002;McCann et al, 2007;Magro et al, 2013).…”
Section: Diagnosismentioning
confidence: 99%